(untitled) (Impetus, 2021)
The present write show the possibles benefits that can write the members and the community in overall of the family’s boxes of compensation, through of leisure experiences that those organisations offer. In this sense, the reflexion carry out in the framework of Colombians CCF and focus in the study case of the family’s compensation boxes comfamilair on the Huila. For these, pick up initially the leisure contemporary perspective in its conception of the humdan experience and then deepen in the framework of CCF of Colombian surrounding and the case of comfamiliar on the Huila. Finally to close mode they analyse and argue the well-being relationship ( such as personal as social) and the leisures experiences that are proportioned by CCF. Any way, this article turn around about the deepeing of the leisure study like contemporary phenomenon with implications in the well-being of the society, starting of proposal strategies by private agents as the CCF in Colombian territory.